Gambaran Pengaruh Merendam Kaki Dengan Air Hangat dan Campuran Kencur Terhadap Keluhan Edema Kaki Ibu Trimester III di Puskesmas Kalidoni Tahun 2025 - Sesilia Triana Dewi; Theresia Shella Beredikta; Martina Astari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
One of the discomforts in pregnant women in the third trimester is leg edema, this occurs as a result of pressure on the uterus which inhibits venous return and the pull of gravity causes greater fluid retention. Non-pharmacological treatment that can be used for pregnant women to reduce leg edema is soaking in warm water mixed with galangal, soaking the feet using warm water mixed with galangal for at least 10 minutes. Soaking at a temperature of 38o for 10 minutes with kencur can reduce muscle tension which makes the body feel more comfortable. The aim of this study was to analyze the effect of a warm water foot soak mixed with galangal on foot edema in third trimester pregnant women. This research used a pre-experiment with a one-group pretest-posttest design with a sample size of 45 pregnant women in the third trimester. This research instrument uses a pitting edema scale questionnaire sheet to measure the degree of leg edema. Data were analyzed the Wilcoxon test to compare pretest and using posttest results. The results of research using the Wilcoxon test obtained a z score of -4.350 with a significance of 0.000 <0.05. This can be interpreted that there is a significant effect of soaking the feet in warm water with a mixture of galangal on foot edema in pregnant women in the third trimester. The mean leg edema before the intervention was 2.9 and the mean after the intervention was 1.5. So it can be concluded that there is an effect of giving warm water foot soaks mixed with galangal on leg edema in third trimester pregnant women.